O florescer do brincar: atravessamentos de uma descoberta por meio de jogos teatrais - MELIK, Raquel da Cunha (2021)
The present study sets out my trajectory, I am the daughter of an extremely protective Lebanese who, during my childhood, did not allow me to play with other children. I started to play as an adult, with other adults, in the Full Degree in Theater of UFPA, when I had contact with the Theatrical Games. They are intended to address some of the possibilities that theatrical games brought to my life, so I use my own trajectory to reveal this discovery. The Methodology used in this study is mainly based on my affective memories, personal reports and the description of my experiences. I narrate important events of my childhood, mainly, about my family relations, until the moment I discover playing, through theatrical games; I present some of the experiences I had during the course activity Stage I and II, where I went to the Youth Theater Course (ETDUFPA) and to the Aimee Semple Mcpherson Elementary School; and development about how the game became part of my life, I mention some of the theatrical games that I like, alternating with concepts of Viola Spolin and Olga Reverbel, for example. I also use research in books, master's thesis, and scientific articles on the proposed theme, thus constituting the bibliographic character of the research. In addition to a semi-structured interview with one of the teachers that stimulated my interest in theatrical games. Concluding, therefore, that theatrical games are like a tool of development of the personal abilities. Of all the benefits that the Theater has brought me, the main one is: PLAY! He also taught me to trust, respect and thank the other, I belong to this place.